Sociocultural Perspective on Teaching Critical Listening through Music in English First Additional Language Classroom - Motlhaka, Hlaviso (International Journal of Language Teaching and Education, 2026)
This study explored how music can facilitate the teaching of critical listening in English First Additional Language (EFAL) classrooms from a sociocultural perspective. Grounded in sociocultural theory, the study examined how music-mediated listening activities support learners’ development of critical listening skills through social interaction, cultural mediation, and collaborative learning (Maniraj, 2026; Nakanishi, 2025). A systematic qualitative review research design was adopted to synthesise evidence from previous studies, theoretical literature, and scholarly discussions on the integration of music in language teaching. The review analysis shows how music serves as a cultural and pedagogical tool that promotes learners’ ability to interpret, analyse, evaluate, and discuss spoken and musical texts critically. Furthermore, the study identified effective pedagogical practices that EFAL teachers can employ to foster critical listening through music-based activities. The findings highlight the role of music in stimulating critical thinking, enhancing learner engagement, and creating meaningful opportunities for dialogue and collaborative knowledge construction. The review also reveals gaps in existing research regarding the explicit teaching of critical listening through music in EFAL contexts. Based on the synthesis of the literature, the study proposes a conceptual framework to guide future empirical research and classroom practice. The study contributes to the growing body of knowledge on innovative language teaching approaches by demonstrating the potential of music as a sociocultural resource for developing critical listening skills in EFAL classrooms.